What Is the Willingness to Receive Vaccination Against COVID-19 Among the Elderly in Italy? Data From the PASSI d'Argento Surveillance System - Contoli, Benedetta; Possenti, Valentina; Minardi, Valentina; Binkin, Nancy J.; Ramigni, Mauro; Carrozzi, Giuliano; Masocco, Maria (Frontiers in Public Health, 2021)
Introduction: Italy was one of the earliest countries to experience a severe COVID-19 epidemic and vaccinating the elderly, who constitute 23% of the population and have experienced the highest mortality rates, is a top priority. Estimating prevalences and understanding risk factors for COVID-19 vaccine hesitancy or refusal are important for development of targeted interventions. Methods: We used data from a specially developed COVID-19 module of PASSI D'Argento, an ongoing surveillance system of residents 65+ years of age to measure the prevalence and identify risk factors for hesitancy and refusal to receive the COVID-19 vaccine. We calculated multinomial regression relative risk ratios to examine the association between demographic characteristics, health status, COVID-19 attitudes and experiences and likely vaccine hesitancy and refusal. Results: Of the 1876 respondents, 55% reported they would accept vaccination and 16% would likely refuse; the remaining 29% were categorized as hesitant. Compared with the acceptance group, we identified several risk factors in common between the hesitancy group and the refusal group, including not having received vaccination against influenza during the previous flu season (hesitancy: RRR = 2.0; 95% CI 1.4–2.9; refusal: RRR = 12.1; 95%CI 7.6–19.4) and lower risk of having had a death from COVID-19 among family or friends (hesitancy: RRR = 4.8; 95%CI 2.0–11.4; refusal: RRR = 15.4; 95%CI 3.7–64.5). The hesitancy group was significantly more likely being worried and they did not know if consequences of the disease would be serious for them. Conclusion: Our findings show the importance of establishing and maintaining active contact between the preventive services, primary care providers and the population because trust is difficult to establish during an emergency like the COVID-19 pandemic. Italian public health is based on a capillary network of general practitioners and having them reach out to their patients who have not previously received influenza vaccine may be a useful strategy for targeting efforts to further encourage uptake of COVID-19 vaccination.